Utilizing the “Plan, Do, Study, Act” Framework to Explore the Process of Curricular Assessment and Redesign in a Physical Therapy Education Program in Suriname - Audette, Jennifer Gail; Baldew, Se-Sergio; Chang, Tony C. M. S.; de Vries, Jessica; Ho A Tham, Nancy; Janssen, Johanna; Vyt, Andre (Frontiers in Public Health, 2017)
PURPOSE: To describe how a multinational team worked together to transition a physical therapy educational program in Paramaribo, Suriname from a Bachelor level to a Master of Science in Physical Therapy (MSPT) level. The team was made up of physical therapy (PT) faculty from Anton De Kom Universiteit van Suriname (AdeKUS), the Flemish Interuniversity Council University Development Cooperation (VLIR-UOS) leadership, and Health Volunteers Overseas (HVO) volunteers. In this case study the process for curricular assessment, redesign, and upgrade is described retrospectively using a Plan, Do, Study, Act framework. METHOD: PT educational programs in developing countries are eager to upgrade to meet international expectations and to better meet community healthcare needs. An ongoing process which included baseline assessment of all aspects of the existing bachelor’s program in physical therapy, development of a plan for a MSPT, implementation of the master’s program, and evaluation following implementation is described. CONCLUSION: Curricular assessment and upgrade in resource-limited countries requires the implementation of process-oriented methods. The Plan, Do, Study, Act process is a useful tool to explore curricular development. The international collaboration described in this paper provides an example of the diligence, consistency, and dedication required to see a project through, and achieve success while providing adequate support to the host site. This project might provide valuable insights for those involved in curricular redesign in similar settings.